Organizational interfaces and innovation: The challenge of integrating supplier knowledge in LEGO systems. Issue 1 (January 2019) - Andersen, Poul Houman; Gadde, Lars-Erik
Abstract: Suppliers have become increasingly important as partners in firms' innovation efforts. Reaping potential collaboration benefits is complex due to challenges in combining internal and external knowledge. The paper explores how various types of organizational interfaces between buyer and supplier create both opportunities and problems for their joint actions. The paper is based on a longitudinal case study of attempts to develop an innovative packaging solution for the toy manufacturer LEGO systems. The study shows that buying firms need to carefully analyse what form of organizational interface access to prioritize since each type offers its specific possibilities and drawbacks. Furthermore, the feasibility of organizational interfaces may change over time due to mutual organizational learning. Highlights: How organizational interfaces affect the outcome of collaborative development and renewal. Transition of organizational interfaces and impact on integration of supplier knowledge in a longitudinal case study. Interface types affects how buyers can activate the resources of the supplier. Core technology transformation processes, enhances need for complex supplier interfaces. Managers must change organizational interfaces over time for integrating supplier knowledge.